Night security with cooler fan / Muhamad Jihan Amirul Zahari, Mohamad Syukri Aqil Mohammad and Mohamad Fadhil Mohamed - Zahari, Muhamad Jihan Amirul; Mohammad, Mohamad Syukri Aqil; Mohamed, Mohamad Fadhil (2015)
This project is called night security light with cooler fan as a prototype, which can implement in house. First of the function, about light which function when detect darkness and the other is cooler fan that can help to control temperature from happen overheating. In this era, problems of waste electrical often occur, many activities people do in their house such as cooking, burning and, supply electric not always function. So this project is created to avoid wasting electricity, make house temperature always under control and can used as an emergency such as blackout. To overcome this problem night security light with cooler fan is created. Cooler fan will turn ON when temperature sensor (LM 35) detect heat about 33°C - 155 °C. Besides that, lamp will lighting ON when Light Dependent Resistor (LDR) detect the darkness. This project is suitable to use at house, hostel, apartment and any residence. The benefit of this project is no need to open fan with manual way because already have automatic cooler fan.